THE USE OF DIGITAL TELEVISION AND ITS CHALLENGES IN PROMOTING CULTURAL LITERACY AND CHARACTER EDUCATION AMONG ELEMENTARY SCHOOL STUDENTS - Ekawati, Santi; Alfiah Junyani Arsyad; Mutmainnah Ismayanti; Sulis Handayani; Abdul Azis Khoiri (PGMI UNHASY, 2026)
Digital television following Analog Switch Off implementation holds strategic potential as a medium for cultural literacy and character formation aligned with Pancasila Student Profile. This research examines content characteristics, stakeholder perceptions, effectiveness factors, and optimization strategies of digital television at SD Yapis An-Nur Sorong City using descriptive qualitative approach through in-depth interviews, observations, and literature review. Findings indicate digital television content is dominated by commercial entertainment programs with minimal educational content, limited cultural programs airing at non-strategic hours, and low stakeholder media literacy. Effectiveness factors include content quality, media literacy, infrastructure accessibility, and policy support. Optimization strategies encompass enhancing educational content with contextual edutainment approaches, developing comprehensive media literacy, systematic integration in active learning, and strengthening multi-stakeholder collaboration to realize digital television as an educational instrument supporting cultural literacy and character formation of Indonesia's young generation.